2017
DOI: 10.1167/iovs.16-21365
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Wound Repair After Rose Bengal and Green Light Crosslinking: Clinical and Histologic Study

Abstract: The healing response in corneas after RGX is very similar to that observed after DE alone, suggesting that, along with its short treatment time and limited effect on keratocytes, RGX displays good potential for clinical cornea stiffening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 44 publications
4
33
1
1
Order By: Relevance
“…In more recent studies, RB 2− phototoxicity to keratocytes in the corneal stroma has been observed and studied , which was consistent with earlier studies showing that R5P 2− photosensitization causes phototoxicity in the same tissue . The reason for greater photocytotoxicity in corneal keratocytes compared with dermal fibroblasts is not clear.…”
Section: Photosensitized Protein Crosslinking Versus Photodynamic Effectsupporting
confidence: 76%
See 1 more Smart Citation
“…In more recent studies, RB 2− phototoxicity to keratocytes in the corneal stroma has been observed and studied , which was consistent with earlier studies showing that R5P 2− photosensitization causes phototoxicity in the same tissue . The reason for greater photocytotoxicity in corneal keratocytes compared with dermal fibroblasts is not clear.…”
Section: Photosensitized Protein Crosslinking Versus Photodynamic Effectsupporting
confidence: 76%
“…In vivo , RB 2− ‐photosensitized crosslinking increased cornea stiffness 1.9‐fold after 1 day and 2.8‐fold after 1 month, as measured by tensiometry and by larger factors when estimated from air puff corneal deformation imaging . Significantly, the same level and depth of stromal cell death was found after RB 2− ‐photosensitized crosslinking as for control eyes that were only de‐epithelialized . When the potential problem of green light damage to the retina was assessed in rabbit eyes, RB 2− ‐photosensitized crosslinking did not cause breakdown of the blood‐retina barrier as assessed by fluorescein angiography and the retina appeared normal histologically .…”
Section: Clinical Applications Of Photochemical Crosslinkingmentioning
confidence: 82%
“…The safety of the treatment was demonstrated through histological analyses showing no thermal damage to retina and iris cells of rabbits after PTB in vivo. 28 Over recent years, more studies on the comparison between collagen crosslinking induced by photo-activated riboflavin and RB on ex vivo and in vivo efficacy, 29 corneal healing response, 30 and collagenase degradation 31 have been performed, showing that treatment with photo-activated RB is more effective than with riboflavin. Based on these results, photo-activated RB to crosslink corneal tissue is considered an attractive therapeutic approach for keratoconus and other disorders and its clinical application in humans should be explored in the near future.…”
Section: Photo-and Sono-activated Rose Bengalmentioning
confidence: 99%
“…Corneal thickness and cell counting were carried out using methods described in a previous study. 22 Briefly, in each cornea, three measurements of corneal full thickness were taken at 340 magnification. Cells were then counted at 3100 magnification using the Touch Count function from Cell A software (Olympus).…”
Section: Cell Countingmentioning
confidence: 99%
“…Cross-linking with RGX involves applying RB onto de-epithelialized corneas for 2 minutes and then exposure to green light (532 nm) for 7 minutes. Both cross-linking protocols have been studied clinically and histologically in animal models, 8,15,21,22 but none of these studies directly compared the two methods.…”
mentioning
confidence: 99%